Achievement of high performance in multi-main-phase (Pr, Nd, MM)-Fe-B sintered magnets by regulating microstructure. (September 2020) - Chen, Hao; Liu, Weiqiang; Yin, Yantao; Li, Zhi; Wang, ZhanJia; Li, Yuqing; Yue, Ming; Pang, Zaisheng; Yu, Xi; Yu, Chunhui
Abstract: Misch-metal (MM) containing four kinds of rare earth elements of La, Ce, Pr and Nd, leads to the complex multi-main-phase (MMP) structure of MM-based sintered magnets. In order to prepare high-performance MM-based sintered magnets, it is necessary to explore the correlation between the microstructure and properties. Here, the MMP [(Pr, Nd)0.65 MM0.35 ]-Fe-B sintered magnets were prepared by the mixtures of MM-free Pr-Fe-B powders and MM-containing (Nd0.5 MM0.5 )-Fe-B powders, and the microstructures of the magnets were controlled by tuning annealing conditions to optimize the magnetic properties. The results show that the continuous RE-rich grain boundary (GB) phases are formed between the adjacent main phase grains by annealing, which is beneficial to weaken the short-range ferromagnetic coupling and improve the coercivity. On the other hand, the inter-diffusion in the main phase grains will take place during the annealing, which makes the composition of the main phase grains to homogenize gradually. Thus, the magnetic impedance effect of the MM-rich grains by the Pr-rich grains is weakened, leading to the reduction of coercivity. Combining these two factors, the MMP [(Pr, Nd)0.65 MM0.35 ]-Fe-B magnet annealed at 420 °C possessing optimal microstructure could obtain excellent magnetic properties of Hcj  = 11.03 kOe and (BH)max  = 38.21 MGOe. Highlights: The excellent magnetic properties are obtained by regulating microstructure. The improvement of coercivity results from the formation of continuous GB phases. Chemical heterogeneity leads to strong magnetic impedance effects between grains. Magnetic impedance effect provides additional help for improving coercivity. The optimized annealing determines continuous GB phases and chemical heterogeneity.